2019
DOI: 10.1155/2019/8360357
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Mandibular Squamous Cell Carcinoma in Intimacy with an Impacted Wisdom Tooth

Abstract: Squamous cell carcinoma is the most common head and neck malignancy. It can occur in the mandible or maxilla without a preexisting oral mucosal lesion. Often, the clinical and radiographic presentation of SCC directs the clinician to favour malignancy over other pathological conditions. However, SCC may also mimic an infectious condition and therefore can pose a diagnostic challenge even for the most experienced clinicians. Herein, we report a case of mandibular squamous cell carcinoma in a 53-year-old male wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Cheung et al reported a case of oral SCC in which signs, symptoms, and initial radiographic findings were compatible with an odontogenic infection associated with impacted wisdom teeth. However, after further analysis, the patient's condition proved to be SCC of the oral cavity [2].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cheung et al reported a case of oral SCC in which signs, symptoms, and initial radiographic findings were compatible with an odontogenic infection associated with impacted wisdom teeth. However, after further analysis, the patient's condition proved to be SCC of the oral cavity [2].…”
Section: Discussionmentioning
confidence: 98%
“…It most commonly occurs on the tongue (40% of cases) and the floor of the mouth (30%). Other sites include the buccal mucosa, gingiva, palate, and retromolar area" [1][2][3]. "Less commonly involved is the gingiva, which comprises about 10% of all OSCCs" [4].…”
Section: Introductionmentioning
confidence: 99%
“…They are the most frequently impacted teeth, and many are associated with cystic changes (up to 50% in some studies), periodontal damage (impacted third molars increased the risk more than 4‐fold) and caries of the distal surface of second molars (up to 12%) 14‐16 . There are conflicting estimates of the frequency of neoplastic lesions associated with third molars, 17‐19 thus casting doubts on claims of necessity to remove third molars to prevent pathological changes 20,21 . This has led to opposing opinions among oral surgeons and general dentists on the indications for third molar removal when presented with periapical radiographs of the same patient 22 .…”
Section: Introductionmentioning
confidence: 99%